Persepsi, Dukungan Dan Hambatan Perawat Dalam Pelaksanaan Perencanaan Pemulangan Pasien di Instalasi Rawat Inap RS Militer Jakarta - Friska Friska; Rr. Tutik Sri Hariyati; Hening Pujasari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: The non-optimal implementation of patient discharge planning is still an important problem in reforming the care system. This non-optimality will have an impact on increasing the length of stay, high patient recurrence rates, and decreasing levels of patient satisfaction and loyalty.Purpose: to explore in-depth experiences of nurses related to nurses' perceptions, support and obstacles in carrying out patient discharge planning.Methods: This research is a qualitative research with a phenomenological approach. Participants in this study were the implementing nurses and team leaders who worked in inpatient rooms. Recruitment of participants is carried out by providing electronic recruitment leaflets to the head of the room. Data analysis used the thematic analysis of the Collaizi method which consisted of six stages, namely preparation of transcripts, coding, categories, themes, interpretation and validation.Results: The results of this study contained 6 (six) themes, namely: 1) The purpose of the patient discharge action plan; 2) The process of carrying out discharge planning at the hospital; 3) SOP for implementation of discharge planning is carried out from the beginning of the patient's treatment; 4) Factors influencing discharge planning; 5) Nurse's motivation in carrying out discharge planning; 6) Obstacles for nurses related to planning to go home which is often overlooked due to the high mobility of nurses and not having time to write.Conclusion: The most important continuity of nursing care activities, one of which is the implementation of discharge planning in accordance with the SOP by involving all health workers and documented from the time the patient enters the treatment room until the patient is planned to go home.Keywords: Patient Discharge Planning, Nursing Care Management, Military Hospital, Qualitative